Predicting student-teacher self-directed learning using intrinsic and extrinsic factors: a Theory of Planned Behavior adoption - Sukkamart, Aukkapong; Pimdee, Paitoon; Leekitchwatana, Punnee; Kongpiboon, Watcharin; Kantathanawat, Thiyaporn (Frontiers in Psychology, 2023)
Introduction This study set out to develop a model that illustrates the causal relationship between factors influencing Thai student-teacher self-directed learning (SDL). To achieve this, the authors analyzed and applied the Theory of Planned Behavior (TPB) to investigate the role of family support, teacher support, friend support, fellow students, and the university in influencing SDL. Methods The research used a sample of 468 student-teachers from five academic majors randomly selected from the King Mongkut’s Institute of Technology Ladkrabang (KMITL) Bachelor of Industrial Education Program during the 2021 academic year. The authors developed a questionnaire which was evaluated from both a panel of experts and a 30 student-teacher pilot test which found that item reliability was acceptable. LISREL 9.10 was used to analyze the data from the study’s structural equation model path analysis. Results The results revealed that all the causal variables in the model positively influenced SDL, explaining the variance of influencing factors on SDL (R2) at 51%. SDL comprised five variables, when ranked in order of importance these were fellow students (FSt), teacher support (TS), family support (FS), friend support (FrS), and their university (Uni). The study also highlighted issues concerning each student-teacher’s learning time management ability and their perception of the university’s ability/willingness to allow each individual to choose their course, thus enhancing their SDL learning ability skills. Discussion It was speculated that some university educators even today perceive SDL as an adult education tool which they perceive is not appropriate at the university level. The authors also felt that for younger student-teachers that the COVID-19 medical emergency limited teacher/student/university interaction, thus contributing to student misconceptions about support availability. This study contributes significantly to the literature by investigating how TPB intrinsic and extrinsic factors impact a university student’s self-directed learning.